ASM handbook. Volume 4E, - Totten, George E. (ASM International, 2016)
This ASM Handbook volume completes the series of volumes on the major technological subject of heat treating. This singular work gives engineers, analysts, and technicians a one-stop source on the wide variety of nonferrous alloys and provides more practical information to guide processing requirements and the necessary background information for those without extensive prior knowledge. Get the basics on heat treating with significantly expanded coverage on nonferrous alloys. In-depth articles provide details on the heat treating principles and practices of aluminum, copper, nickel, and titanium alloys. Quenching, distortion, residual stresses, and alloying effects are given special focus, and attention is given to the complexities of aging practices and microstructural development for the major and less common types of nonferrous alloys.--